Legal Protection in The Implementation of Akad Qardh - Rizki Rahmatullah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
Credit implementation cannot be separated from the agreement and binds the guarantee that given by the debtor. The binding guarantee is carried out by underhand and carried out with notarial deed and PPAT deed. The binding of loan agreements by creditors is inseparable from the rights and obligations of the parties and legal protection of the parties. The problem is about legal standing, forms of protection and problem solving from the implementation of loan agreements. The research methodology used is an empirical juridical approach. The results of this study indicate that the creditor position in the binding agreement that made by underhand becomes weak because the creditor does not get the preference rights if the debtor is default. The implementation of an underhand loan agreement must be carried out perfectly, binding to the notarial deed must be in accordance with UUJN and binding to insurance. Completion of loan agreements with notification, rescue and restructuring of loans with restructuring, composition of loans with litigation and non-litigation, elimination of loans. Advice to Swamitra Minang Alam Sentosa, binding of loan agreements must be carried out with authentic deeds in accordance with UUJN by shared costs, and the insurance accordance with the loan term.